2020
DOI: 10.1088/1741-4326/ab8340
|View full text |Cite|
|
Sign up to set email alerts
|

Numerical simulation of Li-pellet injection experiments for ELM-pacing in EAST

Abstract: Figure 9. Pressure at pedestal top versus time. The parameters for simulation are summarized in table 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 39 publications
2
23
1
Order By: Relevance
“…Compared with the previous study of Li pellets [22] the maximum perturbed pressure resulting from D pellets of the same size is obviously higher, although a D atom only contributes one electron whereas one Li atom contributes three electrons after it has been completely ionized. In Subsection 3.2 we found that increasing the injection velocity would reduce the strength of the density perturbation.…”
Section: Ablation Rates Of D and Li Pellets For Elm Triggeringcontrasting
confidence: 76%
See 4 more Smart Citations
“…Compared with the previous study of Li pellets [22] the maximum perturbed pressure resulting from D pellets of the same size is obviously higher, although a D atom only contributes one electron whereas one Li atom contributes three electrons after it has been completely ionized. In Subsection 3.2 we found that increasing the injection velocity would reduce the strength of the density perturbation.…”
Section: Ablation Rates Of D and Li Pellets For Elm Triggeringcontrasting
confidence: 76%
“…( 1), the space-time varying density of the D atomic number can be evaluated by a method in Ref. [22], which is introduced in the following section.…”
Section: Simulation Details 21 Ablation Modelmentioning
confidence: 99%
See 3 more Smart Citations